2015
DOI: 10.1177/2050312115615365
|View full text |Cite
|
Sign up to set email alerts
|

An observational study comparing the prototype device with the existing device for the effective visualization of invisible veins in elderly patients in Japan

Abstract: Objective:To compare the performance on the detection of the invisible veins between our modified prototype device and an existing device in elderly hospitalized patients.Methods:A prospective, cross-sectional, and observational study was performed in the invisible veins in elderly patients. The major variables, skin color near the invisible veins, and diameter and depth of the invisible veins were measured. The vein visualization rate was calculated as the ratio of the visualized veins to the invisible veins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…From Table 2, Dhakshayani, M. et al, 2015 [47] showed that optimizing the wavelength by utilizing a multispectral IR source, can achieve good visibility of veins considering the types of patients based on color, age and tissue thickness, also the near infrared rays of shorter wavelengths 740, 765 nm exhibits high absorption of light by deoxygenated hemoglobin, with deep penetration at a longer wavelength of 770 and 780 nm. A similar study by Wang F et al, 2013 [50] stated that using multispectral imaging IR with a significant finding that a hairy forearm affects the image of the vein by the formation of a strong reflectance glare while, Kimori et al, 2015 [46] used 850 nm transmitted through the subcutaneous tissue and being compared as deeper than the light source of a commercial vein finder. Another study showed variation in the selected wavelength based on skin color.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From Table 2, Dhakshayani, M. et al, 2015 [47] showed that optimizing the wavelength by utilizing a multispectral IR source, can achieve good visibility of veins considering the types of patients based on color, age and tissue thickness, also the near infrared rays of shorter wavelengths 740, 765 nm exhibits high absorption of light by deoxygenated hemoglobin, with deep penetration at a longer wavelength of 770 and 780 nm. A similar study by Wang F et al, 2013 [50] stated that using multispectral imaging IR with a significant finding that a hairy forearm affects the image of the vein by the formation of a strong reflectance glare while, Kimori et al, 2015 [46] used 850 nm transmitted through the subcutaneous tissue and being compared as deeper than the light source of a commercial vein finder. Another study showed variation in the selected wavelength based on skin color.…”
Section: Discussionmentioning
confidence: 99%
“…In the elderly, vein access was challenging due to the changes in the vein structure as thin and fragile people lose elasticity while pediatrics have smaller peripheral veins with higher content of subcutaneous fat and are usually prone to vasoconstriction. This parameter was also considered in different studies [29,43,46,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 242 subjects/participants were enrolled in the study in the actual in-vitro testing of the developed vein finder device. The subjects’ demographics, such as gender, age, height, and weight for the body mass index (BMI), including the skin tone, were considered as parameters, the same with the previous studies [ 5 , 11 , 13 , 22 , 31 , 38 , 39 , 40 , 41 ], and with the inclusion of arm circumference measurement by the researchers in this study to maximize the assessment process. Specifically, two sites were selected; the arm and dorsal hand for testing, because the subcutaneous veins in the said areas are commonly used for venous blood specimen collection for laboratory testing and intravenous (IV) route for therapy, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In order to perform this procedure, the first step is to make the target vein visible, usually by using a tourniquet or by slightly tapping the site [ 4 ]. However, not all of the veins are visible, because they lack the distinguishing color or venous distention of the skin surface, even after the application of a tourniquet [ 5 ].…”
Section: Introductionmentioning
confidence: 99%